Physical activity – classification, characteristics and health benefits - Piotrowska, Katarzyna; Pabianek, Łukasz (Quality in Sport, 2019)
Regular physical activity is associated with numerous health benefits for both women and men. By regularly engaging in physical activity, we delay overall mortality and improve well-being in any population. The size of the observed adaptive changes resulting from the implemented physical activity is very large, and its benefits are numerous. Appropriate level of physical activity should be maintained throughout life due to its ability to inhibit the natural aging process and slow down the lesions observed with age. The purpose of this work is to illustrate the natural components of physical fitness and physical activity, with particular emphasis on its impact on health and well-being.